Measuring self‐reported quality of life in 8‐ to 11‐year‐old children born with gastroschisis: Is the KIDSCREEN questionnaire acceptable?. Issue 4 (2nd March 2016) - Rankin, Judith; Glinianaia, Svetlana V.; Jardine, Jenni; McConachie, Helen; Borrill, Heather; Embleton, Nicholas D.
Abstract : Background: Children born with gastroschisis have a good prognosis but require surgical correction and long‐term follow up. There has been little research on the impact of gastroschisis on the child's health‐related quality of life (QoL). The aim was to assess face and content validity of the KIDSCREEN‐52 questionnaire as a measurement of self‐ and proxy‐reported QoL in children born with gastroschisis and to evaluate self‐reported QoL in these children compared with the reference population. Methods: In this cross‐sectional exploratory study, we used the validated KIDSCREEN‐52 questionnaire and individual interview with 8‐ to 11‐year‐old children born with gastroschisis who were identified from the Northern Congenital Abnormality Survey. Self‐reported QoL scores were compared with age‐matched UK norms by using the two‐sample t test. Results: Ten children (median age 9.6 years, interquartile range 8.3–11.0) and their parents participated. Children found KIDSCREEN a helpful tool to explore their feelings and that it covered life aspects important to them. Parents believed that all priority areas were represented and that it was straightforward for their children to complete. In nine KIDSCREEN domains, children with gastroschisis had similar QoL scores to those in the reference population, and in one (psychological well‐being) the mean score was significantly better ( p = 0.03). All children described their health as good/very good or excellent; eight said they would not like to change anything about their body. Conclusion: The KIDSCREEN questionnaire has adequate face and content validity as a measure of QoL in children with gastroschisis and is acceptable to both children and parents. Birth Defects Research (Part A) 106:250–256, 2016. © 2016 Wiley Periodicals, Inc.